2014
DOI: 10.1177/1948550614546355
|View full text |Cite
|
Sign up to set email alerts
|

No Longer “All-American”? Whites’ Defensive Reactions to Their Numerical Decline

Abstract: We suggest that Whites’ declining share of the U.S. population threatens their status as the most prototypical ethnic group in America. This prototypicality threat should lead to growing resistance toward diversity, motivated by the desire to reassert Whites’ standing as prototypical Americans. In Study 1, how dramatically Whites perceived their share of the population to decline predicted support for cultural assimilation, mediated by prototypicality threat (controlling for realistic and symbolic threat). Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
237
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 223 publications
(251 citation statements)
references
References 27 publications
12
237
1
1
Order By: Relevance
“…This supports Omi and Winant's (1994) racial formation model by demonstrating how race is relational [77]. My study aligns itself with recent studies [48][49][50]59] showing that white respondents think of Latinos and Blacks similarly, and subscribe to the "model minority" myth when it comes to Asians [50]. The present study helps explain some of the reasons the white respondents in this case study arrive at those conclusions.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This supports Omi and Winant's (1994) racial formation model by demonstrating how race is relational [77]. My study aligns itself with recent studies [48][49][50]59] showing that white respondents think of Latinos and Blacks similarly, and subscribe to the "model minority" myth when it comes to Asians [50]. The present study helps explain some of the reasons the white respondents in this case study arrive at those conclusions.…”
Section: Discussionsupporting
confidence: 88%
“…Most of the literature demonstrates that size matters, because whites become anxious and hostile when they perceive white demographics declining [59]: "a superordinate group (e.g., whites) becomes more racially hostile as the size of a proximate subordinate group increases, which putatively threatens the former's economic and social privilege" [60] (p. 568). Moreover, scholars have specifically addressed issues of language, culture and immigration status, arguing, "the perception of threat to cultural and national homogeneity may give rise, for example, to discriminatory attitudes and anti-immigrant sentiments" [61] (pp.…”
Section: Group Position Theorymentioning
confidence: 99%
“…Through the lens of group threat theory, as the proportion of racial minority group members in a community increases they are perceived as a greater threat to the position held by the dominant group (Quillian, 1995). Recent empirical work confirms that priming participants with the threat of a growing minority out-group increases implicit racial bias (Craig & Richeson, 2014;Danbold & Huo, 2015). Quillian (1995) argues that group threat results from "challenges to the dominant group's exclusive claim to privileges" (p. 588).…”
Section: Discussionmentioning
confidence: 99%
“…Group threat theory proposes that members of the societally dominant group will respond with prejudice when they feel that members of a subordinate group are threatening their position (Quillian, 1995(Quillian, , 1996. Most of the research in this area has focused on relative size of the subordinate group, such that increases in the size of the subordinate group predict increased out-group bias among members of the dominant group (e.g., Danbold & Huo, 2015;Quillian, 1996). For example, people that are primed to think of their group as a statistical minority (e.g., Schaller & Abeysinghe, 2006) demonstrate more out-group prejudice.…”
mentioning
confidence: 99%
“…In line with these findings, in a set of studies with adolescents and young adults in Europe, Verkuyten (2006) found consistently that minority group members supported multiculturalism (implying a complex representation) more than majority group members did. Finally, there is evidence that majority group members and participants who consider their ingroup prototypical of the superordinate group show uneasiness or feel 9 threatened when confronted with the idea of increasing diversity of a superordinate category (Craig & Richeson, 2014;Danbold & Huo, 2015;Ehrke, Bethold, & Steffens, 2014;Outten, Schmitt, Miller, & Garcia, 2012). Complex representations of superordinate categories might be threatening to higher-status groups under some circumstances because they have the potential to eliminate legitimizing beliefs in asymmetric prototypicality by both reducing majorities' and increasing minorities' relative prototypicality.…”
Section: The Current Researchmentioning
confidence: 99%